2017
DOI: 10.3390/molecules22091460
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Methodologies for the Optimization of Lipase and Biosurfactant by Ochrobactrum intermedium Strain MZV101 in an Identical Medium for Detergent Applications

Abstract: The Plackett–Burman design and the Box–Behnken design, statistical methodologies, were employed for the optimization lipase and biosurfactant production by Ochrobactrum intermedium strain MZV101 in an identical broth medium for detergent applications. Environmental factor pH determined to be most mutual significant variables on production. A high concentration of molasses at high temperature and pH has a negative effect on lipase and biosurfactant production by O. intermedium strain MZV101. The chosen mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…As it plays a critical role for maximum physiological activity of bacterial cells and transportation of various nutrients across the cell membranes, it consequently affects the maximum yield of enzymes. Ebrahimipour et al (2017) also reported that the pH is a factor that can affect protein structure and consequently the enzyme activity. It is desirable on an industrial scale, to produce maximum enzyme activity with lower concentration of inoculums.…”
Section: Discussionmentioning
confidence: 99%
“…As it plays a critical role for maximum physiological activity of bacterial cells and transportation of various nutrients across the cell membranes, it consequently affects the maximum yield of enzymes. Ebrahimipour et al (2017) also reported that the pH is a factor that can affect protein structure and consequently the enzyme activity. It is desirable on an industrial scale, to produce maximum enzyme activity with lower concentration of inoculums.…”
Section: Discussionmentioning
confidence: 99%
“…The model generated was found to be statistically significant with a value of 'Probability > F' less than 0.0500 (P < 0.0001), an indication that lipase production could be well described with this model ( Table 3). The F-value (178.26) showed that the model was significant and suitable for simulation of lipase production with any interaction of the five variables [56,57]. There is only a 0.01% chance that a large 'model F-value' could occur due to noise.…”
Section: Selection Of Inducer Oil For Maximum Lipase Productionmentioning
confidence: 99%
“…These two strategies (PBD and followed by a BBD) were implemented to screen and optimize the most important factors lipase and Bs production in Ochrobactrum intermedium [47]. Like with the other examples, the factors that had the greatest effect on production (determined by the PBD) were used for optimization.…”
Section: Mixed Strategiesmentioning
confidence: 99%